2022
DOI: 10.3390/ijms23094791
|View full text |Cite
|
Sign up to set email alerts
|

Functional Screen for microRNAs Suppressing Anchorage-Independent Growth in Human Cervical Cancer Cells

Abstract: The progression of anchorage-dependent epithelial cells to anchorage-independent growth represents a critical hallmark of malignant transformation. Using an in vitro model of human papillomavirus (HPV)-induced transformation, we previously showed that acquisition of anchorage-independent growth is associated with marked (epi)genetic changes, including altered expression of microRNAs. However, the laborious nature of the conventional growth method in soft agar to measure this phenotype hampers a high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 167 publications
1
10
0
Order By: Relevance
“…In earlier research, we showed that both miR‐193a‐3p and miR‐193b‐3p reduce anchorage‐independent growth in SiHa cervical cancer cells 11 . To further understand their role in the regulation of anchorage‐independent growth, we investigated the effect of overexpression of both miRNAs in late passages of FK16A and FK18B cells cultured using adherent plates and ULA plates, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In earlier research, we showed that both miR‐193a‐3p and miR‐193b‐3p reduce anchorage‐independent growth in SiHa cervical cancer cells 11 . To further understand their role in the regulation of anchorage‐independent growth, we investigated the effect of overexpression of both miRNAs in late passages of FK16A and FK18B cells cultured using adherent plates and ULA plates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Anchorage-independent growth was assessed using conventional soft agar assays and on ultra-low attachment (ULA) plates as described before. 11 For colony formation assay, 2500 cells were transfected and seeded in a medium containing 0.35% agarose (Sea-plague agarose; Lonza Group Ltd.) on a surface of 0.6% bottom agarose in a 48-well plate in duplicate. After 3 weeks, colonies exceeding ∼50 cells were counted.…”
Section: Cell Viability Was Measured 72 H After Transfection By Addin...mentioning
confidence: 99%
See 2 more Smart Citations
“…For cell viability measurements, cells were transfected with 2 nM of miRNA mimics and the C2 in 384-well plates using DharmaFECT 4 as the transfection reagent, as described previously. 10 Cell viability was measured using the CellTiter-Glo 3D assay (Promega) following the manufacturer's instructions. Each measurement was performed in duplicate, and cell viability upon miR-129-5p transfection was normalized to the negative control C2.…”
Section: Transfectionsmentioning
confidence: 99%